ANALISIS KEBUTUHAN INDUSTRI KEUANGAN SYARIAH TERHADAP KOMPETENSI LUARAN PENDIDIKAN TINGGI ISLAM - Marliyah Marliyah; Budi Dharma; Muhammad Yafiz; Ahmad Muhaisin B. Syarbaini (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
This study aims to explain the competencies required by Islamic financial institutions today, and how these competencies are fulfilled by Islamic higher education resources, in this case UIN SU Medan. This study also tries to explain how these competencies are obtained both from educational and non-educational processes. The research was conducted with qualitative and quantitative analysis, with the research sample coming from alumni of FEBI UIN SU Medan who work in Islamic financial institutions. Quantitative analysis focuses on justifying user and alumni company perceptions of competence. Qualitative analysis focuses on explaining the relationship between the fulfillment of these competencies in the higher education process. The results show that companies in the Islamic financial institution industry need innovation and critical thinking competencies to be strengthened by Islamic higher education. research by Dharma et al. (2022) who informed the two competencies were also perceived as lacking by other companies. The purpose of financial institutions for competence is in the context of Islamic science, especially in terms of Islamic exploration both from the Qur'an and hadith.